Hot pixel classification of single‐photon avalanche diode detector arrays using a log‐normal statistical distribution - P.W.R. Connolly; X. Ren; R.K. Henderson; G.S. Buller (Electronics Letters, 2019)
CMOS single‐photon avalanche diode (SPAD) detector arrays are commonly used in low‐light imaging applications, and are known to suffer from certain defects which cause ‘hot pixels’. These are detectors which exhibit a significantly larger than average dark count rate, adding noise to the data. Typically, data from these detectors are removed by post‐processing or the detectors can, in some cases, be switched off prior to measurement. Users must define and identify these hot pixels, however there exists no consistent methodology of doing so. The authors present a self‐consistent method of defining a hot pixel by fitting a log‐normal distribution to a histogrammed dark‐count map of the array. The approach has proven a robust method of classifying hot pixels in a number of different detector arrays, providing a threshold based on statistical analysis rather than human intuition. This definition provides a reliable and standardised figure of merit, facilitating a more accurate comparison between different single‐photon detector arrays.